Coated steel and preparation method thereof
By forming a Fe-Ni-Co layer on the steel substrate, controlling the Fe and Co content gradients, and combining with the pulse current nickel-cobalt plating process, the problems of high corrosion resistance and internal resistance of the battery shell material are solved, achieving low cost , high-performance battery case material.
Patent Information
- Application Number
- CN202310784289.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing materials used to prepare battery shells have insufficient corrosion resistance and high internal resistance, making it difficult to meet the comprehensive performance requirements of low cost, low internal resistance and high corrosion resistance.
Fe-Ni-Co coated steel is used to form the Fe-Ni-Co layer on the surface of the steel substrate through plasma sputtering technology, controlling the content and content gradients of Fe and Co, and combining with the pulse current nickel-cobalt plating process, the thickness of the plating layer is optimized. and electrochemical corrosion properties.
The corrosion resistance and low internal resistance of the steel plate are achieved, which reduces the use of coating materials, saves costs, and improves the overall performance of the battery case.
Smart Images

Figure CN119221055A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of coating and plating, and in particular to a coated steel and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of new energy vehicles and other small civilian devices, secondary batteries that can be charged and discharged for a long time have been widely used as power sources. Correspondingly, the material used as the battery shell has also received more and more attention, and the market demand for low-cost and high-performance battery shell materials needs to be met urgently.
[0003] Steel plates with nickel plating on the surface are usually used as battery shell materials due to their corrosion resistance and formability. The battery shell and the battery cover riveted to its opening seal the battery's positive plate, negative plate and separator electrode group and electrolyte in a cylindrical or square battery shell. For most secondary batteries, especially lithium-ion batteries, the negative electrode of the battery is usually connected to the battery shell. In this case, in order to maintain good and stable battery performance, the internal resistance and potential of the battery shell itself also need to be considered. Therefore, it is urgent to develop a battery shell material with excellent comprehensive properties such as low cost, low internal resistance, and high corrosion resistance. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the materials currently used to prepare battery shells have poor corrosion resistance and high internal resistance. In order to achieve this purpose, the present invention provides a coated steel and a preparation method thereof, and also provides a battery shell prepared from the coated steel. The coated steel provided by the present invention and the battery shell prepared therefrom have the characteristics of good corrosion resistance and low internal resistance, and the preparation method is simple, the manufacturing cost is low, and they have good application value and market prospects.
[0005] On the one hand, the present invention provides a coated steel, wherein the coated steel comprises: a steel substrate, and a Fe-Ni-Co layer formed on at least one side of the steel substrate, wherein, in atomic percentage, the Fe content on the surface of the Fe-Ni-Co layer is 1%-10%, preferably 2%-8%, more preferably 4%-6%, and the Co content is 1%-10%, preferably 2%-9%, more preferably 3%-7%.
[0006] In the present invention, the Fe content and the Co content on the surface of the Fe-Ni-Co layer are measured by the following method:
[0007] The plated steel after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering apparatus (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the coating, and then punched out into 10 mm*10 mm samples. The contents (concentrations) of Co, Ni, and Fe on the coating surface in atomic percentages were obtained using Auger electron (AES) spectroscopy analysis (Auger electron spectrometer, model: PHI700, manufacturer: ULVAC-PHI, Japan, using the default instrument parameters).
[0008] When the Fe content on the surface of the Fe-Ni-Co layer is higher than 10%, the excessive Fe content on the surface will reduce the corrosion resistance of the coating; and when the Fe content on the surface of the Fe-Ni-Co layer is lower than 1%, the low surface Fe content is insufficient to harden the coating. Therefore, in the present invention, the Fe content on the surface of the Fe-Ni-Co layer is controlled to be 1%-10%, preferably 2%-8%, and more preferably 4%-6%.
[0009] Adding Co element can effectively reduce the internal resistance of the battery and improve the battery performance. When the Co content on the surface of the Fe-Ni-Co layer is less than 1%, the Co content is too low to obtain a low internal resistance of the coating; and when the Co content on the surface of the Fe-Ni-Co layer is higher than 10%, introducing too much Co into the plating bath will lead to an increase in the precipitate in the plating bath, resulting in unnecessary waste. Therefore, in the present invention, the Co content on the surface of the Fe-Ni-Co layer is controlled to be 1%-10%.
[0010] Preferably, in the Fe-Ni-Co layer, the Fe content gradually increases along the depth direction of the steel substrate on one side of the surface of the Fe-Ni-Co layer, and the position where the Fe content is 20% is set as position A, and the position where the Fe content is 80% is set as position B. From the position A to the position B, the Fe content increases with a content gradient of 5-40% / 1μm, preferably with a content gradient of 10-30% / 1μm, and more preferably with a content gradient of 12-20% / 1μm.
[0011] Preferably, in the Fe-Ni-Co layer, along the surface side of the Fe-Ni-Co layer in the depth direction of the steel substrate, the Co content gradually decreases, and the position where the Co content is 80% of the Co content on the surface of the Fe-Ni-Co layer is set as position X, and the position where the Co content is 20% of the Co content on the surface of the Fe-Ni-Co layer is set as position Y. From the position X to the position Y, the Co content decreases with a content gradient of 2-30% / 1μm, preferably with a content gradient of 5-20% / 1μm, and more preferably with a content gradient of 8-12% / 1μm.
[0012] In the present invention, the content gradient of Fe and Co in the Fe-Ni-Co layer is determined by the following method:
[0013] The plated steel after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering instrument (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the plated layer, and then a sample of about 10mm*10mm perpendicular to the rolling direction was cut from the center part, buried in resin, and polished with 400 mesh, 800 mesh and 2000 mesh in sequence, and then polished and polished with 0.2um 3M81235 polishing liquid for 2 to 10 minutes, and finally etched with 4% nitric acid alcohol etching solution for 20-60s. The cross section was analyzed by Auger electron line analysis at the depth of the coating (Auger electron spectrometer, model: PHI 700, manufacturer: ULVAC-PHI, Japan, using the default instrument parameters) to obtain the content gradient of Fe and Co in the coating cross section.
[0014] Preferably, the thickness of the Fe-Ni-Co layer is 0.5 to 5.3 μm. Within this thickness range, the coating of the present invention can obtain excellent properties such as low internal resistance and corrosion resistance, meet the respective application requirements, and also minimize the use of coating materials and save costs. Preferably, the thickness of the Fe-Ni-Co layer is 1.5 to 5.3 μm, more preferably 2.5 to 4.2 μm,
[0015] In the present invention, the thickness of the Fe-Ni-Co layer is the distance between the surface of the Fe-Ni-Co layer and the position where the total content of Ni and Co decreases to 0. The thickness of the Fe-Ni-Co layer is measured as follows:
[0016] The coated steel sheet after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering instrument (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the coating, and then cut into 10mm*10mm samples, and then the coating thickness was obtained by an X-Ray film thickness tester (fluorescent thickness gauge, manufacturer: FISCHERSCOPE). Specifically, the instrument was preheated, the measurement benchmark was performed, and then the coating was placed at the position to be measured, and the measurement time was about 15 to 30 seconds to obtain the coating thickness.
[0017] Preferably, Fe—Ni—Co layers are formed on both side surfaces of the steel substrate, respectively.
[0018] The steel substrate used in the present invention is not particularly limited, and any steel material capable of forming the Fe-Ni-Co layer of the present invention on the surface can be used. For example, any steel material that meets the manufacturing standards of the battery shell can be used, for example, from the perspective of processability, steel, stainless steel, other alloy steels, etc. can be used; for example, low-carbon aluminum-killed steel with a carbon content of 0.01-0.15% by weight, ultra-low carbon steel with a carbon content of less than 0.003% by weight, or non-aging ultra-low carbon steel with Ti, Nb, etc. added to the ultra-low carbon steel, etc. For example, the steel substrate used can have the following composition (content): C: 0.02-0.065%, 0<Si≤0.03%, Mn: 0.1-0.32%, 0<S≤0.01%, 0<P≤0.02%, Cu: 0.005-0.03%, Ni: 0.005%-0.035%, Cr: 0.015-0.065%, 0<Ti≤0.002%; the balance is Fe and unavoidable impurities.
[0019] The thickness of the steel substrate used in the present invention is not particularly limited and can be appropriately selected according to the purpose after nickel plating. For example, the thickness of the steel substrate can be 0.015 to 1.5 mm. For example, when nickel-plated steel is used to prepare battery shells such as alkaline batteries and coin batteries, the thickness of the steel substrate can be 0.15 to 0.6 mm. When nickel-plated steel is used to prepare alkaline battery shells, the thickness of the steel substrate can be 0.15 to 0.5 mm. If there is a requirement for lightweight and flexibility of nickel-plated steel, the steel substrate can be a foil-like steel substrate with a thickness of 0.015 mm to 0.1 mm.
[0020] The research results of the present invention on the electrochemical corrosion behavior of the coated steel plate with the Fe-Ni-Co layer show that the Fe-Ni-Co layer can effectively inhibit the occurrence of electrochemical corrosion behavior on the surface of the steel plate and can provide the steel plate with excellent corrosion resistance.
[0021] Preferably, the immersion potential of the Fe-Ni-Co layer in a 3.5% sodium chloride aqueous solution is -0.35V to -0.2V, preferably -0.32V to -0.23V, and the corrosion potential of the Fe-Ni-Co layer in a 3.5% sodium chloride aqueous solution is -0.45V to -0.3V, preferably 0.42V to -0.33V. Compared with the comparative example, the immersion potential of the Fe-Ni-Co layer of the present invention is increased by +0.04V to +0.21V, and the corrosion potential is increased by +0.04V to +0.21V. On the other hand, the present invention also provides a battery shell made of the above-mentioned coated steel.
[0022] The surface-treated steel sheet of the present invention can be prepared into various types of battery shells according to different uses by deep drawing, deep drawing and thinning (DI), deep drawing and stretching (DTR), or a process in which deep drawing is followed by stretching and thinning.
[0023] Preferably, the inner wall of the battery case is formed by the Fe-Ni-Co layer of the above-mentioned plated steel. In this case, it is preferred that the Fe-Ni-Co layer satisfies at least one of the following:
[0024] The Fe content on the surface of the Fe-Ni-Co layer is 1%-8%, and the Co content is 5%-10%;
[0025] The thickness of the Fe-Ni-Co layer is 0.5-3 μm.
[0026] Preferably, the outer wall of the battery case is formed by the Fe-Ni-Co layer of the above-mentioned plated steel. In this case, preferably, the Fe-Ni-Co layer satisfies at least one of the following:
[0027] The Fe content on the surface of the Fe-Ni-Co layer is 3%-10%, and the Co content is 1%-8%;
[0028] The thickness of the Fe-Ni-Co layer is 1-5 μm.
[0029] Preferably, the inner wall and the outer wall of the battery case are both formed by the Fe-Ni-Co layer of the above-mentioned plated steel. In this case, it is preferred that the Fe-Ni-Co layer satisfies at least one of the following:
[0030] The Fe content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is different from the Fe content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell. Preferably, the Fe content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is 1% to 8%, and the Fe content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell is 3% to 10%;
[0031] The Co content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is different from the Co content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell. Preferably, the Co content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is 5% to 10%, and the Co content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell is 1% to 8%;
[0032] The Ni content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is different from the Ni content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell. Preferably, the Ni content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is 82% to 94%, and the Ni content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell is 82% to 96%;
[0033] The thickness of the Fe-Ni-Co layer as the inner wall of the battery shell is different from the thickness of the Fe-Ni-Co layer as the outer wall of the battery shell. Preferably, the thickness of the Fe-Ni-Co layer as the inner wall of the battery shell is 0.5 to 3 μm, and the thickness of the Fe-Ni-Co layer as the outer wall of the battery shell is 1 to 5 μm.
[0034] Preferably, the immersion potential of the Fe-Ni-Co layer used as the inner wall of the battery shell in a 3.5% sodium chloride aqueous solution is -0.3 to -0.23 V, and its immersion potential is increased by +0.2-+0.45 V compared with the uncoated steel sheet; the immersion potential of the Fe-Ni-Co layer used as the outer wall of the battery shell in a 3.5% sodium chloride aqueous solution is -0.3 to -0.2 V, and its immersion potential is increased by +0.1-+0.4 V compared with the uncoated steel sheet.
[0035] Preferably, the corrosion potential of the Fe-Ni-Co layer used as the inner wall of the battery shell in a 3.5% sodium chloride aqueous solution is -0.4 to -0.33 V, and its corrosion potential is increased by +0.15-+0.4 V compared with the uncoated steel plate; the corrosion potential of the Fe-Ni-Co layer used as the outer wall of the battery shell in a 3.5% sodium chloride aqueous solution is -0.45--0.33 V, and its corrosion potential is increased by +0.1-+0.35 V compared with the uncoated steel plate.
[0036] The present invention conducts an internal resistance test on the Fe-Ni-Co layer serving as the inner wall of the battery shell, and obtains that the internal resistance of the Fe-Ni-Co layer is 90-100 mΩ. Compared with the comparative example coating, the internal resistance is reduced by 20-30 mΩ, thereby effectively improving the conductivity of the nickel-plated steel.
[0037] On the other hand, the present invention also provides a method for manufacturing the above-mentioned coated steel, wherein the method comprises the following steps performed in sequence:
[0038] (1) providing a steel substrate and pre-treating the steel substrate;
[0039] (2) using a pulse current to plate Ni and Co on a steel substrate to form a Ni-Co coating on the steel substrate;
[0040] (3) Cleaning and drying;
[0041] (4) Continuous annealing to form a Fe-Ni-Co layer on the steel substrate.
[0042] Preferably, the step (2) comprises: plating Ni and Co on the steel substrate using a pulse current with a duty cycle of 1:2 to 1:12, preferably, the duty cycle is 1:5.
[0043] Preferably, the current density of the pulse current is 3 to 15 A / dm 2 If the current density is too low, the productivity may be reduced. If the current density is too high, the current efficiency may be reduced and the coating may be burned. Therefore, the current density of the pulse current is controlled to be 3-15A / dm 2 , preferably 4-12A / dm 2 .
[0044] Preferably, when the Ni-Co coating is used as the inner wall of the battery shell, the current density of the pulse current is 3 to 10 A / dm 2 When the Ni-Co coating is used as the outer wall of the battery shell, the current density of the pulse current is 5 to 15 A / dm 2 .
[0045] Preferably, in step (2), the pulse current is a rectangular wave pulse current (see current waveform diagram Figure 2 , where t represents time and f(t) represents frequency).
[0046] Preferably, the plating bath formula used in step (2) is: NiSO4·7H2O: 200-350 g / L, NiCl2·6H2O: 35-60 g / L, H3BO3: 35-45 g / L, CoSO4·6H2O: 1-20 g / L, additives: 0.05-0.15 g / L.
[0047] Preferably, the pH of the plating bath in step (2) is 3.5-4.0. If the pH of the plating bath is too low, the steel plate is likely to dissolve, and if the pH of the plating bath is too high, the coating is likely to burn.
[0048] Preferably, the plating solution temperature in step (2) is 40-65° C. If the plating solution temperature is too low, the current efficiency may be reduced and the stress may be relatively low. If the plating solution temperature is too high, the anode substrate may be dissolved.
[0049] The Ni-Co coating is annealed to obtain a Fe-Ni-Co layer, and the proportion of Fe element diffused to the coating surface can be adjusted by changing the continuous annealing process parameters. Preferably, the annealing soaking temperature in step (4) is 650-800°C, preferably 680-750°C; the soaking time is 10-300s, preferably 30-220s.
[0050] Preferably, the pretreatment in step (1) includes: chemical degreasing, electrolytic degreasing, cleaning and activation.
[0051] Preferably, chemical degreasing can adopt the following formula and process: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, 0.5ml / L detergent, and the cleaning temperature is maintained at 65±5℃.
[0052] Preferably, the electrolytic degreasing can adopt the following formula and process: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, 0.5ml / L detergent, the cleaning temperature is maintained at 65±5℃, and the current density is maintained at 5A / dm 2 .
[0053] Preferably, the following cleaning process may be used: the steel plate after chemical degreasing and electrolytic degreasing is first cleaned with hot water (50±5° C.), and then cleaned twice with room temperature pure water.
[0054] Preferably, the following activation process can be used: the cleaned steel plate is activated using 50-80 ml / L of H2SO4, the Baume degree of the activation solution is 7-12Be0, and the temperature is maintained at room temperature; after the activation process is completed, it can be washed twice with room temperature pure water.
[0055] Compared with the prior art, the coated steel and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:
[0056] 1. The present invention achieves the characteristics of good corrosion resistance and low internal resistance of the steel plate coating by reasonably designing the Fe content and Co content on the surface of the Fe-Ni-Co layer and the Fe and Co content gradient in the coating, while ensuring sufficient bonding strength between the coating and the steel substrate.
[0057] 2. The present invention obtains a battery shell with excellent performance and saves raw material costs by designing the Fe content, Co content and thickness of the Fe-Ni-Co layer as the inner wall of the battery shell and the Fe-Ni-Co layer as the outer wall of the battery shell differently.
[0058] 3. The present invention adopts pulse current to plate nickel and cobalt, and sets the current duty ratio to 1:2 to 1:12, thereby achieving the effect of uniform deposition of the coating at different current duty ratios.
[0059] 4. The coated steel of the present invention can be used to prepare battery shells for new energy batteries with high requirements for corrosion resistance and internal resistance, meeting the current demand for battery shell materials in the field of new energy vehicles in China, and has good promotion prospects and application value.
[0060] 5. The preparation method provided by the present invention is simple to operate and easy to implement, which simplifies the coating process flow, thereby reducing production costs and has advantages in industrial production and product market promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 Shown is a schematic structural diagram of the coated steel with a Fe-Ni-Co layer in the present invention, wherein A represents the Fe-Ni-Co layer A on the inner wall side, B represents the Fe-Ni-Co layer B on the outer wall side, and C represents the steel plate.
[0062] Figure 2 Shown is a waveform diagram of the pulse current used in the electroplating step of the present invention.
[0063] Figure 3 Shown is a flow chart of the method for preparing coated steel in the present invention. DETAILED DESCRIPTION
[0064] The present invention is described below by specific embodiments, and those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in the present invention. Although the present invention will be introduced in conjunction with a preferred embodiment in the present invention, this does not mean that the features of the present invention are limited to the embodiment. On the contrary, the purpose of introducing the invention in conjunction with the embodiment is to cover other options or modifications that may be expanded based on the claims of the present invention. In order to provide a deep understanding of the present invention, many specific details will be included in the following description. The implementation of the present invention may also not use these details. In addition, in order to avoid confusion or blurring the key points of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0065] In the present invention, the Fe content and the Co content on the surface of the Fe-Ni-Co layer are measured by the following method:
[0066] The plated steel after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering apparatus (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the coating, and then punched out into 10 mm*10 mm samples. The contents (concentrations) of Co, Ni, and Fe on the coating surface in atomic percentages were obtained using Auger electron (AES) spectroscopy analysis (Auger electron spectrometer, model: PHI700, manufacturer: ULVAC-PHI, Japan, using the default instrument parameters).
[0067] The Ni content and Fe content at different depths in the iron-nickel-cobalt layer of the present invention, as well as the Fe content gradient and the Ni content gradient are obtained by the following method:
[0068] The plated steel after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering instrument (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the plated layer, and then a sample of about 10mm*10mm perpendicular to the rolling direction was cut from the center part, buried in resin, and polished with 400 mesh, 800 mesh and 2000 mesh in sequence, and then polished and polished with 0.2um 3M81235 polishing liquid for 2 to 10 minutes, and finally etched with 4% nitric acid alcohol etching solution for 20-60s. The cross section was analyzed by Auger electron line analysis at the depth of the coating (Auger electron spectrometer, model: PHI 700, manufacturer: ULVAC-PHI, Japan, using the default instrument parameters) to obtain the content gradient of Fe and Co in the coating cross section.
[0069] In the present invention, the thickness of the Fe-Ni-Co layer is measured as follows:
[0070] The coated steel sheet after the annealing and alloying step was cleaned for 5 to 10 minutes using a plasma sputtering instrument (model: YZD08, manufacturer: SAT) to remove contaminants (such as oxide layer, etc.) that may be formed on the surface of the coating, and then cut into 10mm*10mm samples, and then the coating thickness was obtained by an X-Ray film thickness tester (fluorescent thickness gauge, manufacturer: FISCHERSCOPE). Specifically, the instrument was preheated, the measurement benchmark was performed, and then the coating was placed at the position to be measured, and the measurement time was about 15 to 30 seconds to obtain the coating thickness.
[0071] Example
[0072] Base steel plate
[0073] The steel plate used in the embodiment has the following composition: C: 0.02-0.065%, 0<Si≤0.03%, Mn: 0.1-0.32%, 0<S≤0.01%, 0<P≤0.02%, Cu: 0.005-0.03%, Ni: 0.005%-0.035%, Cr: 0.015-0.065%, 0<Ti≤0.002%; the balance is Fe and unavoidable impurities.
[0074] Substrate steel plate pretreatment
[0075] Before the electroplating process, the cold-rolled steel sheet is usually pre-treated (with Figure 3 In step S101), the pretreatment includes four steps: chemical degreasing, electrolytic degreasing, cleaning and activation.
[0076] Chemical degreasing formula and process: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, 0.5ml / L detergent, and the cleaning temperature is maintained at 65±5℃.
[0077] Electrolytic degreasing formula and process: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, 0.5ml / L detergent, cleaning temperature maintained at 65±5℃, current density maintained at 5A / dm 2 .
[0078] Cleaning: After chemical degreasing and electrolytic degreasing, the steel plate is first cleaned with hot water (50±5℃), and then cleaned twice with room temperature pure water.
[0079] Activation: The cleaned steel plate is activated with 50-80 ml / L H2SO4. The Baume degree of the activation solution is 7-12 Be0 and the temperature is kept at room temperature. After the activation process is completed, it can be cleaned twice with room temperature pure water.
[0080] Alloy plating Ni-Co
[0081] Ni-Co electroplating process (attached Figure 3 In step S103), the pretreated substrate steel plate is added to the plating bath for alloy plating. The alloy plating bath formula is: NiSO4·7H2O: 200-350g / L, NiCl2·6H2O: 35-60g / L, H3BO3: 35-45g / L, CoSO4·6H2O: 1-20g / L, additive (Rohm and Haas, MP200SE): 0.05-0.15g / L. pH of the plating solution: 3.5-4.0. Plating solution temperature: 45-65°C. Pulse current: duty cycle is 1:5; when powered on, the current density of electroplating on the inner wall of the battery shell is 3-10A / dm 2 ; As one side of the outer wall of the battery shell, the current density of electroplating is 5-15A / dm 2 .
[0082] Washing and drying
[0083] After the alloy plating process, the steel plate was washed three times with pure water at room temperature, then washed once with hot water (50±5°C) and dried.
[0084] Annealing alloying process
[0085] The above alloy Ni-Co coating is alloyed by continuous annealing, and the annealing soaking temperature is controlled to be 650-800°C, and the soaking time is controlled to be 10-300s. After the annealing alloying treatment, a Fe-Ni-Co layer is formed on the surface of the steel plate.
[0086] Electrochemical corrosion testing
[0087] In order to evaluate the corrosion resistance of the above Fe-Ni-Co layer, an electrochemical corrosion experiment on the surface of the coating was carried out using a three-electrode system. The corrosion solution was 3.5wt.% NaCl, a saturated calomel electrode (SCE) was used as the reference electrode, and the experimental temperature was 20-25°C. The size of the experimental sample was 50*70mm. Before the electrochemical corrosion test, all samples were cleaned with ethanol to remove surface oil. The sample was immersed in 1.5L of 3.5wt.% NaCl solution, and the solution temperature was maintained at 25±1°C in a water bath without stirring. The corrosion potential was determined by a potentiodynamic polarization curve (Tafel), which was tested under the premise that the open circuit potential (OCP) was stable. The test potential of the potentiodynamic polarization curve ranged from -200mV vs Eocp to 0.5V, and the scanning rate was about 0.1667mV / s.
[0088] Internal resistance test :Measure surface resistance using the four-probe method. Cut and punch a flat coated steel strip, wipe the surface of the coated steel strip with alcohol and lens-wiping paper to remove fingerprints and oil stains, then use the four pins of a four-probe tester (model: 280SI, manufacturer: Four Dimensions, USA) to touch the surface of the strip, and read the value when it is stable.
[0089] Examples 1-12
[0090] According to the description of the embodiment part above, the following steps are performed: prepare a substrate steel plate and perform pretreatment, perform electroplating according to the process parameters listed in Table 1, and perform annealing according to the annealing process parameters listed in Table 3, and finally obtain a steel plate with a Fe-Ni-Co layer formed on the surface of Examples 1-12, and its thickness, surface Fe content and Co content characteristics are shown in Table 4. Among them, by adjusting the electroplating process parameters and annealing condition parameters, different thicknesses of the coating and different surface Fe content and Co content are obtained. Then, electrochemical corrosion tests and internal resistance tests are performed, and the results are shown in Table 2.
[0091] Comparative Examples 1-4
[0092] The electroplating conditions (shown in Table 1) and annealing conditions (shown in Table 3) when forming the nickel-cobalt alloy plating layer were changed, and the electrochemical corrosion test and internal resistance test results of the nickel-cobalt alloy plating layer of the obtained comparative example are also shown in Table 2. Except for this, the evaluation was performed in the same manner as in Example 1. It should be noted that in Comparative Examples 1-4, the nickel-cobalt alloy plating layer that conforms to the design of the present invention was not formed. The annealing process parameters of Comparative Examples 1-4 are shown in Table 3, and their thickness, surface Fe content and Co content are shown in Table 4.
[0093] As shown in Tables 2 and 4, the thickness of the Fe-Ni-Co layer formed in the examples is 5.3 μm or less, the plating resistance is 100 Ω or less, the immersion potential is -0.33 V or more, and the corrosion potential is -0.45 V or more, which shows that the Fe-Ni-Co layer formed in Examples 1 to 12 has the advantages of low internal resistance and high corrosion resistance. On the other hand, in Comparative Examples 1 to 3, the internal resistance is high and the corrosion resistance is poor, all because the Fe-Ni-Co layer that conforms to the design of the present invention is not formed on its surface, resulting in performance degradation.
[0094] Table 1 Electroplating process parameters of Examples 1-12 and Comparative Examples 1-4
[0095]
[0096]
[0097] Table 2 Electrical conductivity and electrochemical corrosion test results of nickel-plated alloy steel strips of Examples 1-12 and Comparative Examples 1-4
[0098]
[0099] Table 3 Annealing conditions of nickel-plated alloy steel strips of Examples 1-12 and Comparative Examples 1-4
[0100]
[0101]
[0102] Table 4 Characteristics of nickel-plated alloy steel strips of Examples 1-12 and Comparative Examples 1-4
[0103]
[0104]
Claims
1. A coated steel, wherein: The coated steel comprises: a steel substrate, and a Fe-Ni-Co layer formed on at least one side of the steel substrate. In terms of atomic percentage, the Fe content on the surface of the Fe-Ni-Co layer is 1%-10%, and the Co content is 1%-10%.
2. According to the coated steel according to claim 1, in the Fe-Ni-Co layer, along the depth direction of the steel substrate on the surface side of the Fe-Ni-Co layer, the position where the Fe content is 20% is set as position A, and the position where the Fe content is 80% is set as position B, and from the position A to the position B, the Fe content increases with a content gradient of 5-40% / 1μm, preferably with a content gradient of 10-30% / 1μm, and more preferably with a content gradient of 12-20% / 1μm.
3. The coated steel according to claim 1 or 2, wherein: In the Fe-Ni-Co layer, along the surface side of the Fe-Ni-Co layer in the depth direction of the steel substrate, the position where the Co content is 80% of the Co content on the surface of the Fe-Ni-Co layer is set as position X, and the position where the Co content is 20% of the Co content on the surface of the Fe-Ni-Co layer is set as position Y. From the position X to the position Y, the Co content decreases with a content gradient of 2-30% / 1μm, preferably decreases with a content gradient of 5-20% / 1μm, and more preferably decreases with a content gradient of 8-12% / 1μm.
4. The coated steel according to any one of claims 1 to 3, wherein: The thickness of the Fe-Ni-Co layer is 0.5-5.3 μm.
5. The coated steel according to any one of claims 1 to 4, wherein: Fe-Ni-Co layers are formed on both side surfaces of the steel substrate.
6. The coated steel according to any one of claims 1 to 5, wherein: The immersion potential of the Fe-Ni-Co layer in a 3.5% sodium chloride aqueous solution is -0.35V to -0.2V, and the corrosion potential of the Fe-Ni-Co layer in a 3.5% sodium chloride aqueous solution is -0.45V to -0.3V.
7. A battery case made of the coated steel according to any one of claims 1 to 6.
8. The battery case according to claim 7, wherein: The inner wall of the battery case is formed by the Fe-Ni-Co layer of the plated steel. Preferably, the Fe-Ni-Co layer satisfies at least one of the following: The Fe content on the surface of the Fe-Ni-Co layer is 1%-8%, and the Co content is 5%-10%; The thickness of the Fe-Ni-Co layer is 0.5-3 μm.
9. The battery case according to claim 7, wherein: The outer wall of the battery case is formed by the Fe-Ni-Co layer of the plated steel. Preferably, the Fe-Ni-Co layer satisfies at least one of the following: The Fe content on the surface of the Fe-Ni-Co layer is 3%-10%, and the Co content is 1%-8%; The thickness of the Fe-Ni-Co layer is 1-5 μm.
10. The battery case according to claim 7, wherein: The inner wall and the outer wall of the battery case are both formed by the Fe-Ni-Co layer of the plated steel. Preferably, the Fe-Ni-Co layer satisfies at least one of the following: The Fe content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is different from the Fe content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell. Preferably, the Fe content on the surface of the Fe-Ni-Co layer as the inner wall of the battery shell is 1% to 8%, and the Fe content on the surface of the Fe-Ni-Co layer as the outer wall of the battery shell is 3% to 10%; The Co content on the surface of the Fe-Ni-Co layer serving as the inner wall of the battery shell is different from the Co content on the surface of the Fe-Ni-Co layer serving as the outer wall of the battery shell. Preferably, the Co content on the surface of the Fe-Ni-Co layer serving as the inner wall of the battery shell is 5% to 10%, and the Co content on the surface of the Fe-Ni-Co layer serving as the outer wall of the battery shell is 1% to 8%; the thickness of the Fe-Ni-Co layer serving as the inner wall of the battery shell is different from the thickness of the Fe-Ni-Co layer serving as the outer wall of the battery shell. Preferably, the thickness of the Fe-Ni-Co layer serving as the inner wall of the battery shell is 0.5 to 3 μm, and the thickness of the Fe-Ni-Co layer serving as the outer wall of the battery shell is 1 to 5 μm.
11. A method for producing the coated steel according to any one of claims 1 to 6, wherein: The method comprises the following steps performed in sequence: (1) providing a steel substrate and pre-treating the steel substrate; (2) using a pulse current to plate Ni and Co on a steel substrate to form a Ni-Co coating on the steel substrate; (3) Cleaning and drying; (4) Continuous annealing to form a Fe-Ni-Co layer on the steel substrate.
12. The method according to claim 11, wherein: The step (2) comprises: plating Ni and Co on the steel substrate using a pulse current with a duty ratio of 1:2 to 1:12, wherein the current density of the pulse current is 3 to 15 A / dm 2 Preferably, when the Ni-Co coating is used as the inner wall of the battery shell, the current density of the pulse current is 3 to 10 A / dm 2 When the Ni-Co coating is used as the outer wall of the battery shell, the current density of the pulse current is 5 to 15 A / dm 2 .
13. The method according to claim 11 or 12, wherein: The plating bath formula used in the step (2) is: NiSO4·7H2O: 200-350g / L, NiCl2·6H2O: 35-60g / L, H3BO3: 35-45g / L, CoSO4·6H2O: 1-20g / L, additives: 0.05-0.15g / L; preferably, the pH of the plating bath is 3.5-4.0; preferably, the plating solution temperature is 40-65°C.
14. The method according to any one of claims 11 to 13, wherein: In the step (4), the annealing soaking temperature is 650-800° C., preferably 680-750° C.; the soaking time is 10-300 s, preferably 30-220 s.
